Efficacy of enhanced monofocal intraocular lens in combined phacovitrectomy for patients with photoreceptor-preserving epiretinal membrane - Seongyong Jeong; Sunggeun Son; Min Sagong (Scientific Reports)
Abstract The aim of this study is to evaluate the visual outcomes and quality of an enhanced monofocal intraocular lens (IOL), compared to a conventional monofocal IOL in patients with epiretinal membrane (ERM). This retrospective comparative study reviewed medical records of 110 eyes of 110 patients with photoreceptor-preserving ERM (55 patients in each group) who underwent phacovitrectomy and received either a conventional monofocal IOL (Tecnis PCB00) or an enhanced monofocal IOL (Tecnis Eyhance ICB00) from March 2021 to October 2021. Baseline examination included corrected (CDVA) and uncorrected (UDVA) distance visual acuity, and measurement of pupil size. Postoperative evaluation included uncorrected intermediate (UIVA) and near (UNVA) visual acuity, and defocus curve. Contrast sensitivity was assessed using CGT-2000 (Takagi, Seiko, Japan). The baseline parameters showed no difference between PCB00 and ICB00 groups. At 3 months, there was no difference of UDVA and CDVA, but UIVA (0.27 vs. 0.39 LogMAR; p = 0.001) and UNVA (0.35 vs. 0.45 LogMAR; p = 0.014) were better in ICB00 group. On the defocus curve, the ICB00 group demonstrated a slower slope decrease, with higher visual acuity from − 1.5 to -3.0 diopters when compared to the PCB00 group. The distant contrast sensitivity showed no significant difference between two groups. In conclusion, the enhanced monofocal IOL improved intermediate visual outcomes, achieving equivalent distance visual acuity and similar contrast sensitivity to the conventional monofocal IOL. It could be an alternative option to conventional monofocal IOL when planning combined phacovitrectomy for patients with photoreceptor-preserving ERM.